A Novel Green TiO2 Photocatalyst with a Surface Charge‐Transfer Complex of Ti and Hydrazine Groups. Issue 22 (28th March 2017) - Tian, Lihong; Xu, Jilian; Alnafisah, Abrar; Wang, Ran; Tan, Xinyu; Oyler, Nathan A.; Liu, Lei; Chen, Xiaobo
Abstract: The optical property of TiO2 plays an important role in its various and promising photocatalytic applications. Previous efforts in improving its optical properties include doping with various metal and/or non‐metal elements, coupling with other colorful semiconductors or molecules, and hydrogenating to crystalline/disordered core/shell nanostructures. Here, we report a beautiful green TiO2 achieved by forming the charge‐transfer complex of colorless hydrazine groups and surface Ti 4+, which extends the optical absorption into the near infrared region (≈1100 nm, 1.05 eV). It shows an enhanced photocatalytic performance in hydrogen generation under simulated sunlight, and degradation of organic pollution under visible light due to an impurity state (about 0.28 eV) resulting in fast electron–hole separation and injection of electrons from the ligand to the conduction band of TiO2 . This study demonstrates an alternative approach to tune the optical, impurity state and photocatalytic properties of TiO2 nanoparticles and we believe this will spur a wide interest in related materials and applications. Abstract : Green with envy : The formation of a surface charge‐transfer complex of Ti and hydrazine gives TiO2 a beautiful green color. This green TiO2 shows enhanced photocatalytic performance in hydrogen generation under simulated sunlight. It also leads to degradation of organic pollution under visible light due to an impurity state that is created above the valence band and results in injection of electrons from the ligand to the conduction band of TiO2 (see figure).